Efektivitas Penerapan Model Project Based Learning Pada Materi Sistem Sirkulasi Manusia Terhadap Hasil Belajar Siswa SMA St. Maria Tarutung - Chrystyne Angelyn; Halim Simatupang; Dermawan Sianipar (Program Studi Pendidikan Biologi, 2021)
This study aims to decide the effectiveness of the application Project Based Learning model on student learning result in the human circulation system material in class XI IPA SMA Santa Maria Tarutung. This type of research is a pre-experimental study using a one group pretest-posttest design. The sampling technique was determined through purposive sampling technique with a sample totaling 36 students. The data collection technique used was through pre-test and post-test. The results showed that the increase in student learning outcomes was 48.11%. The results of the data analysis showed that the pre-test mean score was 34.44 and the post-test score was 82.55. Based on the results of learning skills (Product), it was found that the skill scores with very good criteria were 13 students, 12 students good criteria and 11 students good enough criteria. The level of student learning completeness is 86.11% (complete), the level of student mastery of the material is 82.55% (high) and the average N-Gain shows that student learning outcomes have increased by 74.16% (high). From this research it can be concluded that the application of the Project Based Learning model is effective when used when learning online.